The Cortisol Awakening Response In Children and Adolescents with a Parental History of Anxiety - Helleman, Amanda (Université d'Ottawa / University of Ottawa, 2016)
Objective: The current study used a high risk design to investigate whether the Cortisol Awakening Response (CAR) is a potential heritable trait marker of anxiety disorder risk. Method: The sample consisted of 274 healthy offspring (7-18 years old) including 101 offspring with a parental history of panic disorder (PD), generalized anxiety disorder (GAD), or social anxiety disorder (SAD) and 173 offspring with no parental psychopathology. Salivary cortisol was collected at wake-up, 30, and 60 minutes later, as well as at 4pm and 8pm on two consecutive days. The CAR was calculated using area under the curve with respect to ground (AUCg) and increase (AUCi). Correlation analyses of covariates were conducted. Results: No differences between high and low risk groups were detected when the combined sample of high risk offspring was examined. However, when anxiety disorder subtypes were considered, offspring with parental GAD or SAD had a significantly lower CAR and diurnal cortisol response than those with no parental psychopathology. No differences in the CAR or diurnal cortisol were found in offspring with parental PD. Age and puberty status correlated negatively with AUCg and awakening values and anxiety sensitivity correlated positively with AUCg and awakening values. Conclusions: A blunted CAR and diurnal cortisol response may represent a possible heritable risk marker that is specific to GAD or SAD. Further research is needed to confirm these findings. Study results may have important implications in identifying children at risk for anxiety disorders and creating early interventions intended to change the trajectory of risk.
Keywords: Cortisol; Anxiety; Risk; Children; CAR